Purple hibiscus - Adichie, Chimamanda Ngozi, 1977- (London : Harper Perennial, 2005)
A teenaged Nigerian girl and her older brother struggle to cope with life in their tense, stifling household--caused by their father's demands for perfection--after getting a taste of freedom during a visit to their aunt's home.
Keywords: Brothers and sisters -- Fiction; Fathers and daughters -- Fiction; Teenage girls -- Fiction